Antenatal Anxiety in Pregnant Women Undergoing Cesarean Section - Saima Ashraf, Sanober Faisal, Zill E Huma, Nida Nadeem, Aamir Khan, Fareeha Shahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: frequency of antenatal anxiety in pregnant women undergoing cesarean section Methodology: A total of 100 patients fulfilling selection criteria were enrolled in the study through OPD Department of Obstetrics & Gynaecology, Nishter Medical University, Multan. Demographical information like age, gestational age and parity was recorded. All the cases were evaluated through The Hamilton Anxiety, rating scale (HAM-A) and positive cases (anxiety) were recorded on a pre-designed proforma as described in operational definitions. Severity of anxiety was also recorded. Patients with anxiety were managed as per standard protocols. Results: In our study, of 100 cases, mean age as 30.45+5.02 years, mean gestational age was 39.35+1.17 weeks, mean parity was 2.34+0.93, mean Hamilton Anxiety Rating scale of the patients was 17.48+7.42 with minimum 3.00 and maximum 30.00. Frequency of anxiety status of the patients shows that 13(16.3%) had no anxiety, 29(36.3%) had mild, 20(25%) had moderate and 18(22.4%) had severe anxiety. Practical Implication: determination of the antenatal anxiety in pregnant women undergoing cesarean section would help in the prevention and early management of anxiety in our population. Conclusion: According to this study, 16.3% of pregnant women undergoing cesarean section had antenatal anxiety Keywords: Pregnant women, cesarean section, elective, emergency antenatal anxiety, Hamilton Anxiety, rating scale